Automatic Water Level Control Tandon Air Berbasis Arduino Uno - Khairil Anam; Achmad Fathoni Rodli (Puslitbang Sinergis Asa Professional, 2022)
Problems that arise when the level of water level in the water reservoir tandon is unknown because there can be a state of overflowing or empty Tandon due to a lack of control of the Tandon. In this study, an Arduino Uno-based water level control tool was made using ultrasonic sensors as a water level detector and equipped with a buzzer alarm that has a function to signal a sound when the water is full or empty, and the tools made in this study are equipped with LCD features to display indicators of the volume of water in the Tandon. After the design of the tool is completed, then the analysis test of the tool series is carried out which aims to see the success rate of the entire system after carrying out the tool design process. As well as testing tools are carried out to take data as a reference in the system analysis process. Of all the stages of designing and testing automatic water level prototypes.